GENITIC DIVERSITY OF AN ENDEMIC MEDICINAL ORCHID, COELOGYNE NERVOSA A. RICH. FROM SOUTHERN INDIA USING MORPHOLOGICAL AND MOLECULAR MARKERS - J. RAMUDU,; S.M. KHASIM, (International Journal of Pharma and Bio Sciences, 2013)
Genetic diversity of an endemic medicinal orchid, Coelogyne nervosa A. Rich. was investigated by using SDS-PAGE, RAPD markers and morphological characters. C. nervosa is growing as epiphyte as well as lithophytes in Eastern and Western Ghats of India. It is an important medicinal orchid showing antioxidant and anticancer properties. Leaf samples collected from these two reference sites were taken for RAPD and protein profile analysis. The objective of this study is to assess the genetic diversity of endemic orchid C. nervosa distributed in southern India. The six populations collected from these two geographical regions exhibited significant variation in their morphological and molecular characters. The stomata are tetracytic and hypostomatic in distribution. The maximum thickness of cuticle and midrib region in leaf and, extensive lignification in exodermis and endodermis of root were recorded in populations located in Western Ghats as compared to those of Eastern Ghats. It is interpreted to be associated with the conservation of water. RAPD and protein profile data showed the inter population diversity between these two reference sites. This can be attributed to the ecological and climatic conditions prevailing in the Eastern and Western Ghats of India.